The effect of date palm juice on increasing hemoglobin (HB) in pregnant women at the Sadar Jaya Community Health Center, Bengkalis Regency - Juyanti Lamhotria Naibaho; Fajar Sari Tanberika; Fatma Nadia; Nurhidaya fitria (International Journal of Health Engineering and Technology, 2026)
Anemia due to iron deficiency is the main cause of anemia in pregnant women. In 2024, 843 pregnant women underwent ANC at the Sadar Jaya Health Center, of which 129 or approximately 56% experienced anemia. This study aims to determine the effect of date palm juice on increasing hemoglobin (Hb) in pregnant women at the Sadar Jaya Health Center, Bengkalis Regency. This type of research is pre-experimental. The population was all pregnant women in the first trimester in March 2026, totaling 30 people, the sampling technique was total sampling. Data analysis used the t-test. The results showed that the hemoglobin (Hb) levels in pregnant women before being given date palm juice were mostly 18 respondents (57.2%) with moderate Hb levels. The hemoglobin (Hb) levels in pregnant women after being given date palm juice were mostly 20 respondents (66.7%) with mild Hb levels. The effect of date palm juice on increasing Hemoglobin (Hb) in pregnant women with a ρ value of 0.000 <0.05. The conclusion of this study is that there is an effect of date palm juice on increasing Hemoglobin (Hb) in pregnant women at the Sadar Jaya Community Health Center, Bengkalis Regency. Therefore, it is hoped that the community health center will increase knowledge and understanding, especially in providing services to pregnant women regarding the prevention of anemia by providing date palm juice to pregnant women in the first trimester.